'The City of the Eye': Urban Aesthetics and Surveillance in the City of Venice. (28th April 2015) - Whybrow, Nicolas
<x content-type="archive" xml:space="preserve">Abstract</x> Joseph Brodsky's assertion in Watermark (1992) that Venice 'is the city of the eye', providing a sense of security and solace to inhabitants and visitors via the sheer aesthetic force of its surroundings, implicitly raises questions, in the context of the twenty-first-century city, about the performative nature of not only modern-day urban aesthetics but also surveillance in public space, both of which, as phenomena, are dependent on forms of visual observation. Taking into account contemporary Venice's complex make-up in terms of its transient and permanent populations – tourists, economic migrants, and local residents – and the central issue facing the city of the gradual erosion of its historical infrastructure owing to excesses of commercialism and the material effects of flooding, in this article Nicolas Whybrow ponders the continuing role of aesthetics in an urban context. In particular, he considers how both Brodsky's perception of the effects of the historical environment and contemporary instances of artistic intervention or engagement with the city – official (as part of the globally renowned Biennale) and unofficial (in the form of graffiti writing) – might position users of public space in the light of increased attempts to implement formal controls in the interests of security. Nicolas Whybrow is Associate Professor (Reader) and Head of Department in the School of Theatre, Performance, and Cultural Policy Studies at the University of Warwick. His most recent books are Art and the City (2011) and, as editor, Performing Cities (2014).